Analisis Personal Hygiene pada Penyajian Makanan di Pasar Segar Panakkukang Kota Makassar - Khiki Purnawati Kasim; Juherah Juherah; Fitriyah Fadhilah Rahmadani; Rostina Rostina; Muh. Saleh (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The outbreak of food poisoning in Indonesia was ranked second as the most frequent non-natural disaster in 2018. The Food and Drug Supervisory Agency or BPOM Makassar recorded hundreds of cases of food poisoning in South Sulawesi Province during 2021.Panakkukang Fresh Market in Makassar City which is a culinary tourism area, in terms of personal hygiene, there are still many traders who do not use personal protective equipment and make direct contact with food without using gloves when processing and serving food. The purpose of this research is to find out personal hygiene in serving food at pasar Segar Panakkukang in Makassar. The type of research used is descriptive observational using the Slovin formula to determine the sample size of 28 respondents. The result of this study indicate that from 28 traders who have good personal hygiene as many as 2 respondents (7,1%) and not good personal hygiene as many as 26 respondents (92,9%) and in serving food that has good food presentation as many as 16 respondents (57,1%) and not good food presentation as many as 12 respondents (42,9).The conclusion of this research is that personal hygiene of food vendors in fresh marketing is included in the bad category whilethe food serving is in the good category. This research recommend food handlers to pay moreattention to personal hygiene and use personal protective equipment as well as for further researchers it is recommended to confirm the personal hygiene variabels that have the most influence on the contamination of jackfruit food. Keywords : Personal hygiene, food serving.